Enhancing students’ critical thinking through video-based PBL: A classroom action research in Grade XI - Hidayatus Sholihah; Moh. Wahyu Kurniawan; Anisah Hariati (Jurnal Pendidikan Profesi Guru, 2024)
This Classroom Action Research aimed to enhance the critical thinking skills of Grade XI students at SMA Negeri 3 Malang in the subject of Civic Education (PPKn) through the implementation of Problem-Based Learning (PBL) supported by instructional videos. The main issue addressed was the low level of students’ critical thinking, attributed to the suboptimal use of learning media, which led to monotonous lessons and limited student engagement. The study was conducted in two cycles, each consisting of one session, involving 36 students (23 males and 13 females). The findings showed a significant improvement in both cognitive and skill aspects of critical thinking. In Cycle I, 22 students (60%) achieved the minimum mastery level in knowledge, increasing to 33 students (92%) in Cycle II. For skills, the number of students meeting the mastery criteria rose from 17 (47%) in Cycle I to 34 (92%) in Cycle II.These results indicate that the integration of video-assisted PBL is effective in improving students’ critical thinking skills in Civic Education.